MODERN APPROACHES TO PRESCHOOL EDUCATION AND FAMILY COOPERATION - Ismailova Gulmira; Toshtemirova Sevinch (PT. Antis International Publisher, 2024)
This article talks about the fact that the family is the main link of society, that it is a small state within states, that the development of society also begins precisely with this small link, skillfully combining preschool educational organizations with parents in the form of collective and one-on-one work, achieving positive results in raising children due to the organization